A STUDY ON STUDENTS' ABILITY IN UNDERSTANDING ANNOUNCEMENT TEXT AT TENTH GRADE OF SMAS NURUL IKHLAS SUNGAI RAYA - Herma Padhilah; Melda Yeni; Juni Mahsusi (J-Shelves of Indragiri (JSI), 2024)
The problem of this research was the Tenth Grade students of SMAS Nurul Ikhlas Sungai Raya feel difficult to answer some questions relate to announcement text. Therefore, the purpose of this research is to know “Students' ability in Understanding Announcement Text”. This research was descriptive quantitative research. The researcher was distributing test to 18 respondents to answer the purpose above. The sample was taken by using total sampling, because the sample is limited. After collecting the data, the researcher found that students’ ability in understanding announcement text at Tenth Grade of SMAS Nurul Ikhlas Sungai Raya is in low level. It can be seen from the mean score of students’ test that is 54.75. It means that their ability in understanding announcement text still needs improvement.